PERENCANAAN JEMBATAN BETON BERTULANG DUSUN I DESA PULAU GADANG KECAMATAN XIII KOTO KAMPAR - Alisa Putra, Agus; Riyan Sabri, Muhammad; Setiawan, Beny (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
This study focuses on the structural redesign of a collapsed 34-year old wooden bridge in Dusun I Kampung Mahligai, Pulau Gadang Village, XIII Koto Kampar District, Riau Province. The original structure served as a critical access route for pedestrians and vehicles. The redesign adopts reinforced concrete with an 8-meter span and a width of 3,5 meters, incorporating guardrails, sidewalks, deck slabs, and girders. Structural calculation follow RSNI T-12-2004 and RSNI T-02-2005 standards, with manual internal force analysis. The design specifications include guardrails (10x15 cm, 2D10 reinforcement), sidewalks (20cm thickness, D12-120), deck slabs (20cm thickness, D12-150), and girders (30x60 cm, 12D19). A central pillar supports the span, ensuring improved stability and longevity.Keywrods: Bridge Redesign; Reinforced Concrete Structure; Structural Analysis.